THE IMPLEMENTATION OF ROSETTA STONE SOFTWARE TO IMPROVE STUDENTS’ LISTENING SKILL - Devi Nur Puspitasari (English Education Department Slamet Riyadi University Surakarta, 2019)
This research aims at improving listening skills using Rosetta Stone Software media at SMPN 27 Surakarta class VIII D. This method was Class Action Research. in this study there were two cycles and post tests. in each cycle there were four procedures, they plan, act, observe and reflect. In collecting the data consists of tests and non-tests. The test was written tests, and non-tests like; observe, interview and documentation.The results of the implementation of Rosetta Stone software was improvent from pre test, post test 1 and post test 2. The mean score pre test is 65.00, in post test 1 is 73.00. and post test 2 is 76.00. in cycle 2 the use of Rosetta Stone Software made the students feel happy, active, relaxed, more confident, and increases students' learning motivation in the teaching and learning process. Key words :Listening Skill, Rosetta Stone Software, Classroom Action Research.